(untitled) (Nonlinear Studies, 2023)
In the present manuscript, we establish some fixed point results for pairs of weakly compatible mappings satisfying certain rational type contraction in C^*-algebra valued metric space. To check the usability of the results, some illustrative examples have been provided at the last.